A rare case of Raoultella planticola urinary tract infection in an immunocompromised patient with multiple myeloma - William Paul Skelton, IV (IDCases, 2017)
Introduction: Raoultella planticola is a gram-negative rod associated with soil and aquatic environments that has rarely been associated with human infections. Presentation of case: We present the case of a 73 year old female with multiple myeloma and recurrent Clostridium difficile infection who was found to have a urinary tract infection with Raoultella planticola, which has only been reported to cause 29 cases of human infections and 2 cases of urinary tract infections. Discussion and conclusion: Our case and literature review suggest that immunocompromised patients are predisposed to developing Raoultella planticola infection, and that this is a potential emerging pathogen.